Evaluating the Weathering Effect on Granite, Limestone and Uncrushed River Stone Aggregates for Road Constructions - Ron Buking, Ron Aldrino Chan @; Anthony, Lwinsky Brina; Edwin, Ervin Rangga; Tirau, Larry Silas; Bujang, Zamri; Wan Ibrahim, Wan Hashim (International Journal of Integrated Engineering, 2023)
The lack of excellent aggregate materials has become a major issue in Sarawak. River stone, abundant in many places of Sarawak, can be used as an alternative aggregate material, minimising the reliance on high-quality aggregates like granite in the production of an affordable and sustainable road pavement. Weathering also deteriorates aggregate materials. This project aims to investigate the durability of granite, limestone, and uncrushed river stone aggregates with regards to weathering effects. The aggregates are subjected to two conditions, i.e., normal condition (without wetting and drying cycles) and wet-dry condition (with wetting and drying cycles). The physical properties of aggregates are determined by the Flakiness Index, Elongation Index, and Specific Gravity. Weathering effects on aggregates are determined using laboratory tests such as Aggregate Impact Value (AIV), Aggregate Crushing Value (ACV), and Los Angeles Abrasion (LAA). Weathering cycles have been found to have a minor impact on aggregates in the short term. Overall, the test results indicate that wetting and drying circumstances have a negligible effect on aggregates over a short period of time. The materials' physical attributes all meet JKR requirements. The Aggregate Impact Value (AIV), Aggregate Crushing Value (ACV), and Los Angeles Abrasion (LAA) values are nearly constant across the wet-dry state for all aggregate kinds. Despite the wet-dry situation, the AIV, ACV, and LAA tests demonstrate that specific aggregate materials retain their durability when compared to other aggregate materials. As a result, granite is the most durable aggregate in terms of AIV and LAA when compared to limestone and uncrushed river stone, while uncrushed river stone is more durable in terms of ACV when compared to granite and limestone.